Perceptions and practices on newborn care and managing complications at rural communities in Bangladesh: a qualitative study - Abu Sayeed Md. Abdullah; Koustuv Dalal; Masuma Yasmin; Gainel Ussatayeva; Abdul Halim; Animesh Biswas (BMC, 2021)
Abstract Background Community misperception on newborn care and poor treatment of sick newborn attributes to neonatal death and illness severity. Misperceptions and malpractices regarding neonatal care and neonatal complications are the leading causes of neonatal deaths in Bangladesh. The study was conducted to explore neonatal care's perceptions and practices and manage complications among Bangladesh's rural communities. Methods A qualitative study was conducted in Netrakona district of Bangladesh from April to June 2015. Three sub-districts (Upazilas) including Purbadhala, Durgapur and Atpara of Netrakona district were selected purposively. Five focus group discussions (FGDs) and twenty in-depth interviews (IDIs) were conducted in the rural community. Themes were identified through reading and re-reading the qualitative data and thematic analysis was performed. Results Community people were far behind, regarding the knowledge of neonatal complications. Most of them felt that the complications occurred due to lack of care by the parents. Some believed that mothers did not follow the religious customs after delivery, which affected the newborns. Many of them followed the practice of bathing the newborns and cutting their hair immediately after birth. The community still preferred to receive traditional treatment from their community, usually from Kabiraj (traditional healer), village doctor, or traditional birth attendant. Families also refrained from seeking treatment from the health facilities during neonatal complications. Instead, they preferred to wait until the traditional healers or village doctors recommended transferring the newborn. Conclusions Poor knowledge, beliefs and practices are the key barriers to ensure the quality of care for the newborns during complications. The communities still depend on traditional practices and the level of demand for facility care is low. Appropriate interventions focusing on these issues might improve the overall neonatal mortality in Bangladesh.